2020
DOI: 10.1523/jneurosci.0954-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Protect Human Dopaminergic Neurons from α-Synuclein Accumulation and Propagation

Abstract: The pathologic hallmark of Parkinson's disease is the accumulation of a-synuclein-containing Lewy bodies/neurites almost exclusively in neurons, and rarely in glial cells. However, emerging evidence suggests that glia such as astrocytes play an important role in the development of a-synuclein pathology. Using induced pluripotent stem-derived dopaminergic neurons and astrocytes from healthy subjects and patients carrying mutations in lysosomal ATP13A2, a monogenic form of synucleinopathy, we found that astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…This led to increased production of IL-1β and suggested that there is a direct link between the astrocyte lysosome and neuroinflammation in PD ( 71 ). Lysosomal degradation was also shown using human iPSC, from healthy controls or from patients carrying a mutation in lysosomal ATP13A2 , which were differentiated into midbrain dopamine neurons and astrocytes ( 72 ). This study showed that astrocytes rapidly internalised α-syn and when they were co-cultured with neurons, this led to a decreased accumulation of α-syn in neurons and as a consequence diminished interneuronal transfer of α-syn.…”
Section: Astrocytes and Their Role In Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This led to increased production of IL-1β and suggested that there is a direct link between the astrocyte lysosome and neuroinflammation in PD ( 71 ). Lysosomal degradation was also shown using human iPSC, from healthy controls or from patients carrying a mutation in lysosomal ATP13A2 , which were differentiated into midbrain dopamine neurons and astrocytes ( 72 ). This study showed that astrocytes rapidly internalised α-syn and when they were co-cultured with neurons, this led to a decreased accumulation of α-syn in neurons and as a consequence diminished interneuronal transfer of α-syn.…”
Section: Astrocytes and Their Role In Parkinson's Diseasementioning
confidence: 99%
“…This study showed that astrocytes rapidly internalised α-syn and when they were co-cultured with neurons, this led to a decreased accumulation of α-syn in neurons and as a consequence diminished interneuronal transfer of α-syn. Interestingly, loss of this protective function of astrocytes was seen with ATP13A2 deficiency, suggesting that this gene function in astrocytes, contributes partially to PD pathology ( 72 ).…”
Section: Astrocytes and Their Role In Parkinson's Diseasementioning
confidence: 99%
“…Moreover, experiments with iPSC-derived astrocyte-neuron co-cultures revealed that astrocytes rapidly internalize neuronal a-SYN. By contrast, this intercellular transfer was prohibited in cultures from PD patients with mutations in the lysosomal storage protein ATP13A2 (135). This data not only suggests that astrocytes contribute to the neuronal a-SYN pathology in genetic PD, but that they may also act as mediators in neuroinflammatory processes.…”
Section: Astrocytes and Mitochondria In Inflammationmentioning
confidence: 80%
“…However, the effects of pathogenic α-synuclein species on astrocytes have not been thoroughly studied. Previous work has shown that astrocytes can protect dopaminergic neurons from α-synuclein deposition and degeneration (54). However, α-synuclein aggregates are also frequently observed in PD patients, where they disturb vital homeostatic functions and thereby exacerbate disease pathology in neurons (55).…”
Section: Discussionmentioning
confidence: 99%